Thermal conductivity of suspended single crystal CH3NH3PbI3 platelets at room temperature - Shen, Chao (2020)
Recently, organic–inorganic lead halide perovskites have gained great attention for their breakthrough in photovoltaic and optoelectronics. However, their thermal transport properties that affect the device lifetime and stability are still rarely explored. In this work, the thermal conductivity properties of single crystal CH3NH3PbI3 platelets grown by chemical vapor deposition are studied via non-contact micro-photoluminescence (PL) spectroscopy. We developed a measurement methodology and derived expressions suitable for the thermal conductivity extraction for micro-sized perovskites. The room temperature thermal conductivity of ∼0.14 ± 0.02 W m−1 K−1 is extracted from the dependence of the PL peak energy on the excitation laser power. On changing the film thickness from 80 to 400 nm, the thermal conductivity does not show noticeable variations, indicating the minimal substrate effects due to the advantage of the suspended configuration. The ultra-low thermal conductivity of perovskites, especially thin films, suggests their promising applications for thermal isolation, such as thermal insulation and thermo-electricity.